Social Incompetence of Learners with Insecure Attachment Styles: A Multiple Case Study of Three Secondary Schools in South Africa - SIBANYONI, Morefaith Naledi; ALOKA, Peter J.O. (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2026)
The study aimed to examine social incompetence of learners with insecure attachment styles in three secondary schools in South Africa. The study employed a multiple case-study research design. The sampling frame comprised 27 participants, including 6 life orientation teachers, 18 grade 10 learners, and 3 deputy principals from 3 specifically chosen secondary schools in the Sedibeng West district. Data collection for this study involved the utilization of open semi-structured interviews. The data obtained from semi-structured interviews was evaluated thematically, using research questions as a framework. The results indicated that learners with social incompetence exhibited low self-esteem, antisocial behaviours, aggressive behaviours, poor anger control, poor interpersonal skills, lack of emotional competence, and external locus of control. The study recommends that parents should be trained on best parenting programs and increase awareness in the community on secure homes.